(3QSGdI aj CMcGe GdUdGIs - (3GdOQGRj GdHMQGfj, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J (B1168s
(3ChdgG (B:s
(3MeOG ddg Ydi fYeGFg (B... (3bO cKQ Ydi GdJeGS LedI ef GdENhGf GdeDefjf hGdMdGf GdWGdHjf ddMb hGdjbjf aj JUfja QSGdI aj CMcGe GdUdGI GdJj gj YehO GdOjf dcf Ydi hLg GdEjLGR hGdGNJUGQ ef ZjQ GWGdI (B...s
(3BNQgG (B:s
... (3GdNGeSI jSJMH LHQ GdebUhQI HGdJSHjMGJ GdCQHY aj OHQgG KdGKjf eQI hGdCUd aj gPG GdMce QhGjI SdjeGf Hf MaU GdeQhRj bGd bGd Gdabjg GdYScQj Ydjg GdSdGe jLH Ydi GdeSGaQ (B...(3hgPG eG SeMJ Hg GdbQjMIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8\215s
(3GdPQjYI (B15\427s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis